Faktor-Faktor Yang Mempengaruhi Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual (Studi Pada Pemerintah Daerah Kabupaten Boyolali) - Purwaningrum, Idha; , Drs. Atwal Arifin, M.Si., Akt., CA (2017)
The study aims to determine the effect of the quality of human resources, use of information technology, organizational commitment and communications on the application of the accrual-based government accounting standards at the the government of boyolali regency. The sampel was SKPDs Boyolali which includes in financial department staff. The sampling technique is done by purposive sampling with a sample of 160 respondent. Data analysis using multiple linear regression analysis. These results indicate that the variable the use of information technology a significant effect on the application of the accrual-based government accounting standards. While the quality of human resources, organizational commitment and communication does not significantly influence the implementation of accrual-based SAP.